Analysis of Accounting Digitalization Transformation on the Financial Performance of Msmes in Cirebon City - Sri Rahayu; Firman Hidayat (Greenation International Journal of Economics and Accounting, 2025)
The MSME (Enterprise, Micro, Small and Medium) ecosystem in Indonesia has undergone significant changes as a result of the digital revolution period. Therefore, the financial performance of MSMEs has a very important role for the national economy, considering that this sector is the backbone of economic growth. Cirebon City as one of the centers of economic growth in West Java Province reflects positive developments in the MSME sector. This study uses a descriptive quantitative approach to analyze the relationship between accounting digitalization transformation variables and the financial performance of MSMEs through objective and systematic measurements. The population in this study includes all MSMEs registered and operating in the city of Cirebon. The results show that the implementation of digital accounting systems in MSMEs significantly improves operational efficiency, especially in terms of reducing the amount of time needed to process financial transactions and reducing the number of errors made manually. the results and implications of this study should be used taking into account the limitations of its scope and methodology. It is hoped that this limitation will be the basis for future researchers to develop quantitative and qualitative approaches, in order to produce a more comprehensive understanding of the impact of digitalization in accounting practice.